Design And Development Of Guardrail For Exclusive Motorcycle Lanes - Biliyamin, Ibitoye Adeoye (2007)

(untitled)
The use of roadside barrier, especially W-beam guardrail has been demonstrated in various studies to have performed satisfactorily for protecting occupants of cars and trucks. However, its usage for motorcycle impact has been given little consideration. Thus, the safety of motorcyclists in relation to this barrier has become a major concern to road safety experts. Early studies have identified that motorcycle impact with this guardrail would result in severe injuries to the motorcyclists. However, relatively few studies have addressed the safety implication of this guardrail on motorcyclists. Presently, no studies have been reported to have specifically designed alternative guardrail for protecting motorcyclists especially along exclusive motorcycle lanes. In view of this problem, this study focuses on the design and development of safer guardrail system that can replace the existing W-beam guardrail being used along exclusive motorcycle lanes, as exists in Malaysia. This design required use of computer modelling and simulation as main tool and the conduct of a physical crash test to validate the baseline simulation model. Furthermore, the input parameters for the validated model were used for subsequent simulation of motorcycle crash on guardrail with 18 impact conditions. Results of this simulation were used to establish the design criteria. Based on the established design criteria alternative models were developed on the basis of achieving the design target; mainly to reduce potential injury risks to rider. The alternative models were combined to form 24 alternative models that were optimized in order to select the best model for the new guardrail design. The new guardrail design consists of metal plate (grade 13 steel) of 2.28 mm thick, wider and continuous surface that has a high degree of flexibility that enables soft redirection of the rider. It is also comparable to the existing guardrail in ease of construction and installation and can have a potential to utilize economical end-treatment techniques. The effectiveness of the new design was evaluated using the same computer simulation program – MADYMO. The outcome demonstrated that severity of head injury risk can be reduced significantly if impact of head to the ground can be prevented. The high flexibility of the new guardrail prevents the rider from having head impact with ground. Thus, the results show that HIC and head acceleration values could be reduced by 96% and 91% respectively for a typical crash scenario of 48km/h impact speed on the guardrail orientated at 45 degree and 4m post spacing. The major conclusions of the study are that modification of the configuration and material of the existing guardrail can significantly reduce potential injury risks to motorcyclists and that the new guardrail is safer to replace the existing guardrail along exclusive motorcycle lanes.